FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA PEMBERIAN ASI EKSLUSIF DI WILAYAH PESISIR, KECAMATAN KAJANG, KABUPATEN BULUKUMBA - Sri Ningsih; Kurniati Akhfar; Sri Rosmawar; Miftahul Jannah (Journal Of Midwifery And Nursing Studies, 2020)
Health development programs in Indonesia are still prioritized on efforts to improve the health status of mothers and children. The groups that are vulnerable to health are pregnant women, mothers giving birth and babies during the perinatal period. This is indicated by the high maternal mortality rate, and infant mortality rate. The general purpose of this paper is to determine the factors that influence the low level of exclusive breastfeeding in the coastal area of Kajang sub district, Bulukumba Regency in 2015. This type of research is a descriptive analytic design with a cross sectional design. The results of the research above are based on the aspect of understanding, it can be seen that the high socio-cultural culture of mothers in giving breast milk to their babies is by looking at the number of respondents as many as 32 (80%) who understand the importance of exclusive breastfeeding for infants and only 2 respondents who are in the poor category